A review of the notion of historical memory: memory-history dichotomy, differences between legal and historical truth and associated dilemmas - Fray Esteban Atehortúa-Aguirre (RHS Revista Humanismo y Sociedad, 2020)
The aim of this paper is to provide a review of the concept of historical memory, how it arose and developed historically since World War II, as well as to highlight the shift caused by the concept of memory in the field of historiography and in the political arena. It also seeks to understand why the reconstruction of historical memory processes and political-ideological and epistemological dilemmas posed by them are relevant today, as well as their relationship with the issue of truth (both legal and historical), long understood using the subject-object schema. The research uses a hermeneutic-analytic approach to the analysis of bibliographic sources. From these sources, the study examines the issue of truth in historical memory, as well as the differences between legal truth and historical truth that converge in historical memory projects. Historical memory is important in contemporary societies, which see in memory building processes, linked to violations of human rights and human dignity, a potential for reconciliation, pacification and restitution for victims, through the protection of the right to truth, justice, reparation and non-repetition.